2013
DOI: 10.1371/journal.pone.0060271
|View full text |Cite
|
Sign up to set email alerts
|

Critical Transitions in Early Embryonic Aortic Arch Patterning and Hemodynamics

Abstract: Transformation from the bilaterally symmetric embryonic aortic arches to the mature great vessels is a complex morphogenetic process, requiring both vasculogenic and angiogenic mechanisms. Early aortic arch development occurs simultaneously with rapid changes in pulsatile blood flow, ventricular function, and downstream impedance in both invertebrate and vertebrate species. These dynamic biomechanical environmental landscapes provide critical epigenetic cues for vascular growth and remodeling. In our previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 68 publications
0
50
0
Order By: Relevance
“…The fifth arch pair have been have been termed to describe arteries that are only temporarily present in early development of the chick embryo, and are not considered a major PAA (Hiruma and Hirakow, 1995). Proper arch formation depends on programmed processes but is also regulated by blood flow conditions (Keller et al, 2007; Pekkan et al, 2008; Kowalski et al, 2013). …”
Section: Normal Heart Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth arch pair have been have been termed to describe arteries that are only temporarily present in early development of the chick embryo, and are not considered a major PAA (Hiruma and Hirakow, 1995). Proper arch formation depends on programmed processes but is also regulated by blood flow conditions (Keller et al, 2007; Pekkan et al, 2008; Kowalski et al, 2013). …”
Section: Normal Heart Formationmentioning
confidence: 99%
“…To this end, research that integrates hemodynamic data with biological change in response to hemodynamics, and the mechanisms behind this response, are essential. Several studies to determine hemodynamics in the developing embryonic heart are have been recently published (McQuinn et al, 2007; Stekelenburg-De Vos et al, 2007; Liu et al, 2012; Kowalski et al, 2013; Shi et al, 2013), as well as studies to look at remodeling and changes in tissue properties shortly after interventions and flow exposure (Groenendijk et al, 2007; Biechler et al, 2010; Yalcin et al, 2011; Buskohl et al, 2012; Tan et al, 2013). As these two aspects of cardiac development are put together, a more complete picture of heart formation is emerging where developmental programming plays a substantial role, which needs to be better characterized and studied.…”
Section: Conclusion and Future Suggestionsmentioning
confidence: 99%
“…This allows the experimenter to modulate the embryonic environment during growth (e.g., inducing hypoxia at controlled levels). When these two attributes are combined with the relatively large size of the embryos of some avian species, it becomes apparent that avian embryos have allowed invasive experimental manipulations (Burggren et al, 2004;Kowalski et al, 2013;Shell et al, 2016). Such invasive procedures have primarily focused on the embryo of the chicken but also the embryos of other birds such as the emu (Dromaius novaehollandiae) and ostrich (Struthio camelus).…”
Section: Ontogeny Of Cardio-respiratory Morphology Physiology Biochmentioning
confidence: 99%
“…Changes in WSS patterns are detected through endothelial cells, which convert mechanical stimuli into intracellular signals, leading to an increase or decrease in vessel diameter (Bayer et al, 1999; Girerd et al, 1996; Langille and O’Donnell, 1986). Recent studies of the Hamburger-Hamilton (HH) stage 18, 21, and 24 PAA have revealed clear relationships between PAA flow, WSS, and luminal growth (Kowalski et al, 2013; Wang et al, 2009). While the asymmetric PAA regression pattern has been shown to occur by differential apoptosis (Molin et al, 2002), the expression of genes that normally orchestrate left/right asymmetry has not been observed in the PAA (Liu et al, 2002; Yashiro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%